The Study of Code Mixing on Melaney Ricardo’s Video Youtube Channel Sociolinguistics Approach - Br Siahaan, Julita; Johan, Muhammad (Humanitatis : Journal of Language and Literature, 2020)
This research investigated about code-mixing that found in YouTube. This article used a You Tube, because many people nowadays used YouTube to express their creativity. The aims of this study were to find out the types of code-mixing and the code-mixing category dominantly used by Melaney’s utterance in her videos. The researcher used Hoffman theory to reveal this study. The research applied qualitative descriptive method to analyze the types. of code-mixing and the category dominantly used by Melaney’s utterance. The method of collecting data was observation. The data were taken from video that are published in YouTube. The result of this research there are (20) intra-sentential mixing, (8) intra-lexical mixing, (2) involving a change of pronunciation. They all have different levels of code-mixing used in Melaney’s utterance. The conclusion is You Tube as a social media that allows users to share photos and videos, entertainment, tutorials, introduce or promoting a product, and access world’s information by using this application. Keywords: Sociolinguistics, Code-mixing